Moana the essential guide - Bazaluda, Barbara (London Dorling Kindersley Limited, 2016)
Find out everything you need to know about the newest Disney heroine, Moana, and her hero Maui, on their incredible journey across the South Pacific. Discover the beautiful locations of Oceania, including breathtaking underworlds along with frightening sea creatures! This book is packed with stunning images of Moana's quest and provides a fascinating, in-depth look at the most thrilling moments from the movie
Comic strips
Keywords: Comic -- stories